2014
DOI: 10.1016/j.energy.2014.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Energy saving potential of semi-transparent photovoltaic elements for building integration

Abstract: Within the building energy saving strategies, BIPV (building integrated photovoltaic systems) present a promising potential based on the close relationship existing between these multifunctional systems and the overall building energy balance. Building integration of STPV (semi-transparent photovoltaic) elements affects deeply the building energy demand since it influences the heating, cooling and lighting loads as well as the local electricity generation. This work analyses over different window-to-wall ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 37 publications
(23 reference statements)
1
44
0
6
Order By: Relevance
“…As a result of applying the developed methodology to the Gangnam district in Seoul, South Korea, the physical, geographic (i.e., the available rooftop area), and technical potentials of Gangnam district were 9,178,982 MWh, 4,964,118 m 2 , and 1,130,371 MWh [82]. Second, there have been various studies on the BIPV [83][84][85][86][87][88][89][90][91][92][93][94][95]. Olivieri et al (2014) evaluated the technical performance of the window-integrated semi-transparent PV system and general glazing via a package of specific software program (i.e., DesignBuilder, EnergyPlus, PVsyst, and COMFEM).…”
Section: Part B-1: Renewable Energy (Re)mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of applying the developed methodology to the Gangnam district in Seoul, South Korea, the physical, geographic (i.e., the available rooftop area), and technical potentials of Gangnam district were 9,178,982 MWh, 4,964,118 m 2 , and 1,130,371 MWh [82]. Second, there have been various studies on the BIPV [83][84][85][86][87][88][89][90][91][92][93][94][95]. Olivieri et al (2014) evaluated the technical performance of the window-integrated semi-transparent PV system and general glazing via a package of specific software program (i.e., DesignBuilder, EnergyPlus, PVsyst, and COMFEM).…”
Section: Part B-1: Renewable Energy (Re)mentioning
confidence: 99%
“…Second, there have been various studies on the BIPV [83][84][85][86][87][88][89][90][91][92][93][94][95]. Olivieri et al (2014) evaluated the technical performance of the window-integrated semi-transparent PV system and general glazing via a package of specific software program (i.e., DesignBuilder, EnergyPlus, PVsyst, and COMFEM). It was confirmed that the window-integrated semi-transparent PV system showed 18-59% energy savings according to the façade opening compared with the reference glass [90].…”
Section: Part B-1: Renewable Energy (Re)mentioning
confidence: 99%
See 1 more Smart Citation
“…They built an experimental set-up to thermally, optically and electrically characterize different kinds of amorphous silicon semi-transparent glasses [14]. They used the experimental data obtained as input of a dynamic building simulation model to evaluate the energy saving potential of STPV elements with different gradation of transparency in Madrid, comparing the results with the energy performance of a standard glazing system [15]. Liao et al [16] evaluated the energy performance of STPV using amorphous silicon with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This activity, commonly named as Building Integrated Photovoltaics (BIPV), combines the architectural integration of the PV modules with renewable electricity generation in buildings. The optimization of these elements from the electrical, thermal and optical points of view will improve the building energy efficiency [1]. According to the current European regulations about the energy performance of buildings and energy efficiency, such as Directives 2010/31/EU, and 2012/27/EU, respectively [2,3], the energy performance of buildings should be calculated on the basis of a methodology which consider thermal characteristics, adequate natural lighting, heating and air-conditioning installations, application of energy from renewable sources, passive heating and cooling elements, shading, indoor air-quality, and design of the building.…”
Section: Introductionmentioning
confidence: 99%